Nursing student's perceptions, satisfaction, and knowledge toward utilizing immersive virtual reality application in human anatomy course: quasi-experimental - Samar Thabet Jallad; Israa Natsheh; Lareen Abu Helo; Dania Mahmoud Ibdah; Amna Salah; Rasha Muhsen; Younes Shehadeh; Naeem Froukh (BMC, 2024)
Abstract Background A paradigm shift in nursing education is required to prepare Z generation of nursing students through integrated innovative technologies as teaching strategies such as immersive virtual reality in several bioscience and main courses to facilitate and enhance learning process. Aim/objective Examine the effect of utilizing an immersive virtual reality application on students' perceptions, knowledge, and satisfaction in an anatomy course. Methods A quasi-experimental (pre-post test, one group) design was conducted among 1st year nursing students (N = 138) enrolled in an anatomy course in the spring semester of 2023-2024 in the nursing program in the health professions faculty at Al-Quds University. The technology acceptance model (TAM) was used for data collection. Results The results showed that 96% of participants were satisfied with using the VR application, and it retains their knowledge in the human anatomy course. 92% of the total, were under the age of twenty, and 84% were females. 80.1% (2.99 ± 0.58) of those students had more positive perspectives of VR applications in the nursing courses. Additionally, there were significant differences in students' satisfaction and knowledge toward using VR applications after the anatomy lecture (p = 0.029, p = 0.05, respectively). Conclusion Virtual reality is a supplemental innovative tool for promoting learning. Nursing students perceive immersive virtual reality technologies positively and prefer using three-dimensional images in their anatomy courses, which helps them recall their knowledge, understand concepts of educational content, identify learning objectives, and improve learning outcomes. This study found that virtual reality can improve nursing students' understanding, satisfaction, and knowledge of anatomy.